Application of cold atmospheric plasma for mold inactivation - Petra Tichá; Mária Domonkos; Zuzana Rácová; Pavel Demo (Acta Polytechnica CTU Proceedings)
Mold growth in indoor interiors is an increasing problem that has adverse effects on both occupants and building materials. The aim of this study was to present the new environmentally friendly method (cold atmospheric plasma treatment) for decontamination of indoor environments contaminated by mold spores, with the potential to become an effective replacement for conventional methods, such as ultraviolet-C (UV-C) germicidal irradiation. The spores of Aspergillus species on malt extract agar plates were exposed to plasma produced by diffuse coplanar surface barrier discharge. The surface coverage of mold was evaluated using image analysis. Cold plasma treatment inactivated spores on the surface of the culture medium in 0.5 min, whereas a weak growth delay was observed after 30 minute exposure to UV-C irradiation. This study demonstrated that cold atmospheric plasma is a more effective method for reducing mold spores on agar compared with germicidal UV-C irradiation.